Risk Oriented Supplier Selection Model Based on Fuzzy Cluster Analysis and Fuzzy Analytic Hierarchy Process - APRIANSYAH NIM 23415031 , FIRMAN
Globalization and the development of information technology have laid the foundation to the new era of business that are steps ahead in complexity and risk. Sustainability of a business depends on how it is able to adapt to uncertainty and competition. Relationship with supplier is one of the increasingly complex aspect of the new era. Decisions regarding supplier have become more strategic and risky. History has shown how the problems related to supplier would disrupt the business process of an enterprise. Increasing dependency and the inherent risk really threaten the continuity of a business. Therefore, it is not just about efficiency anymore, it is also about sustainability. These factors have raised concerns regarding supplier related risk, which subsequently drive efforts to develop robust supply system that is capable of withstanding any kinds of disruptions. This research tries to accomodate such aspiration by developing a model, in regard to supplier selection, that is able to provide a platform for risk management in relation with supplier. This research employs, within the model, cluster analysis method collaborated with MCDM technique in assessing the risks of the suppliers, in order to present the acceptable alternatives of suppliers to be selected. The final step is then to select the best supplier from the least risky group of suppliers based on benefit or cost related criterias using MCDM technique. This research also attempts to provide flexibility for enterprise to employ sourcing strategy related to the number of supply sources. A supplier selection model which accomodates supplier risk assessment and prototype of the decision support system based on the model developed are among the results of the research. The advantage of the model is the capability of accomodating both absolute scale, that tends to be objective and tangible, and relative scale, which most of the time subjective and intangible. As for the downsides, this model is still tested using hypothetical data, and has not considered the modelling of supplier development process and also multi-item sourcing. From the research conducted, it can be concluded that the model developed can be used in supplier selection with the consideration of supplier risk as an attempt to improve sustainability of a business or organization. The model developed is based on Fuzzy Cluster Analysis and Fuzzy AHP as the foundation to model risk oriented decision making in the case of supplier selection.